2023
DOI: 10.3390/v15030626
|View full text |Cite
|
Sign up to set email alerts
|

Re-Emerged Genotype IV of Japanese Encephalitis Virus Is the Youngest Virus in Evolution

Abstract: An outbreak of viral encephalitis caused by a Japanese encephalitis virus (JEV) genotype IV infection occurred in Australia between 2021 and 2022. A total of 47 cases and seven deaths were reported as of November 2022. This is the first outbreak of human viral encephalitis caused by JEV GIV since it was first isolated in Indonesia in the late 1970s. Here, a comprehensive phylogenetic analysis based on the whole genome sequences of JEVs revealed it emerged 1037 years ago (95% HPD: 463 to 2100 years). The evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
5
6
0
Order By: Relevance
“…In one of the last studies, Xu et al (2023) reported a JEV GI-GV substitution rate (95% HPD, 1.62×10 −4 –3.97×10 −4 ) comparable with our estimates. Notably, the sample size (115), clock model (UCLD) and tree prior (Bayesian Skyline) applied in the work of Xu et al (2023) were similar to two previously discussed studies with significantly lower JEV substitution rates (Pan et al, 2011; Gao et al, 2015). The possible explanation is that Xu et al (2023) provide new JEV nucleotide sequences, however without testing at least the measure of clock-like evolution by RTT, the question about the true factor of distorted inference of substitution rate persists unresolved.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In one of the last studies, Xu et al (2023) reported a JEV GI-GV substitution rate (95% HPD, 1.62×10 −4 –3.97×10 −4 ) comparable with our estimates. Notably, the sample size (115), clock model (UCLD) and tree prior (Bayesian Skyline) applied in the work of Xu et al (2023) were similar to two previously discussed studies with significantly lower JEV substitution rates (Pan et al, 2011; Gao et al, 2015). The possible explanation is that Xu et al (2023) provide new JEV nucleotide sequences, however without testing at least the measure of clock-like evolution by RTT, the question about the true factor of distorted inference of substitution rate persists unresolved.…”
Section: Resultssupporting
confidence: 91%
“…Despite the relatively large number of complete ORF sequences used in our study, the uncertainty in the assessment of the evolutionary timescale of the entire tree spans a large time interval (95% HPD of root height, 407–2333 years). A little more accurate estimates of time to MRCA of JEV GI-GV (95% HPD, 463–2100 years) were reported by Xu et al (2023) with a sample size of 115 complete genome sequences. In the other studies with smaller sample sizes, 95% HPD intervals for tree roots were much wider: Gao et al (2015) conclude that the MRCA of JEV GI-GV is estimated to have occurred 3255 years ago (95% HPD, 978–6125 years); Pan et al (2011) studied JEV GI-GIV defined the MRCA age of the entire clade as 1695 years ago (95% HPD, 548–3153 years).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These aspects are relevant and require further investigations considering that during the recent outbreak of JEV in Australia in 2021/2022 over 80 piggeries were affected [73]. Interestingly, this outbreak was caused by a recently emerged genotype IV virus [74], which had a high mutation rate, possibly enabling a fast virus evolution and adaptation [75]. To our knowledge it is not known whether direct transmission events between pigs took place in Australia and whether the characteristics of the virus changed during the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of JEV currently circulating in Australia was detected in the Tiwi Islands, Northern Territory (NT), in February 2021, and one year later in other states of Australia (Sikazwe et al, 2022). However, it is estimated that the Australian clade emerged six years ago, suggesting that this clade of GIV viruses had been cryptically circulating in Australia for several years (95% HPD, 2–14) (Xu et al, 2023). There were 45 human cases of this vaccine-preventable disease recorded during 2022, including seven deaths.…”
Section: Introductionmentioning
confidence: 99%